Evaluating the impact of Kampus Mengajar Program: a comparative study of student literacy and numeracy skills outcomes - Ditasona, Candra; Junsay, Merle; Purba, Santri Chintia; Pardosi, Deborah (Universitas Terbuka, 2025)
Indonesia's literacy and numeracy competencies remain critically low despite marginal improvements in PISA scores from 2018 to 2022, which paradoxically declined overall. To address this educational crisis, the Indonesian government launched the Kampus Mengajar program, deploying university students to enhance primary school literacy and numeracy outcomes. This study evaluates the effectiveness of the Kampus Mengajar program by analyzing changes in students' Minimum Competency Assessment (MCA) performance. A pre-experimental design was employed with 30 fifth-grade students from SDN 13 East Jakarta, selected through purposive sampling. Data collection occurred over four months using pre-test-post-test instruments, supplemented by classroom observations. Statistical analysis was conducted using SPSS, including descriptive statistics, Shapiro-Wilk normality tests, and paired t-tests. The findings reveal significant improvements in both literacy and numeracy MCA scores following the Kampus Mengajar intervention. Statistical analysis confirmed meaningful differences between pre-test and post-test performance, demonstrating the program's positive impact on student competencies. The research identified that enhanced teaching methodologies and additional academic support contributed to measurable learning gains. This study contributes empirical evidence supporting the effectiveness of collaborative university-school partnerships in addressing Indonesia's literacy and numeracy challenges. The results suggest that the Kampus Mengajar model represents a viable strategy for educational improvement. However, successful implementation requires adequate school infrastructure and resources. Future research should investigate the long-term sustainability of these improvements and explore optimal teaching methodologies within the Kampus Mengajar framework to maximize elementary students' MCA outcomes.